SIKAP TERHADAP SAINS SISWA DALAM PENERAPAN PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY APPROACH) - Arriestina, Nova Arriestina; Nor, Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aims to determine the increase attitudes toward science of students in physics learning by the implementation of guided inquiry approach in class X IPA4 SMA Muhammadiyah 1 Pekanbaru. The subjects are students of class X IPA4. This class has fewer than 35 students, consists of 13 male students and 22 female students. The data collection instrument in this study is questionnaire of attitudes towards science which consists of 24 statements. Analysis of the data in this study is a descriptive analysis using the Gain (increase). If G>0.3, so the attitudes towards science of student is increase by the implementation of guided inquiry approach. The results showed: Gain attitudes towards science of students on aspects of interest in the science of 0.15 with a low category, aspects of science and learning activities of 0.17 with a low category, the importance of science aspects of 0.20 with a low category, and environmental aspects of the view science of 0.18 with a lower category. So that the average gain attitudes toward science of students in the amount of 0.18 to a low category. Application of guided inquiry approach the material and application of Newton's laws have low gain to improve attitudes toward science of students in class X SMA Muhammadiyah 1 pekanbaru. Key Words : attitudes towards science, attitude, guided inquiry approach, Gain.